The folding competence of HIV-1 Tat mediated by interaction with TAR RNA. Issue 7 (3rd July 2017) - Kim, Jung Min; Choi, Hee Sun; Seong, Baik Lin
ABSTRACT: The trans-activator Tat protein of HIV-1 belongs to the large family of intrinsically disordered proteins (IDPs), and is known to recruit various host proteins for the transactivation of viral RNA synthesis. Tat protein interacts with the transactivator response RNA (TAR RNA), exhibiting RNA chaperone activities for structural rearrangement of interacting RNAs. Here, considering that Tat-TAR RNA interaction is mutually cooperative, we examined the potential role of TAR RNA as Chaperna – RNA that provides chaperone function to proteins - for the folding of HIV-1 Tat. Using EGFP fusion as an indirect indicator for folding status, we monitored Tat-EGFP folding in HeLa cells via time-lapse fluorescence microscopy. The live cell imaging showed that the rate and the extent of folding of Tat-EGFP were stimulated by TAR RNA. The purified Tat-EGFP was denatured and the fluorescence was monitored in vitro under renaturation condition. The fluorescence was significantly increased by TAR RNA, and the mutations in TAR RNA that affected the interaction with Tat protein failed to promote Tat refolding. The results suggest that TAR RNA stabilizes Tat as unfolded, but prevents it from misfolding, and maintaining its folding competence for interaction with multiple host factors toward its transactivation. The Chaperna function of virally encoded RNA in establishing proteome link at the viral-host interface provides new insights to as yet largely unexplored RNA mediated protein folding in normal and dysregulated cellular metabolism.